1981
DOI: 10.3109/03008208109152132
|View full text |Cite
|
Sign up to set email alerts
|

Fibril Diameters in the Extracellular Matrix of the Periodontal Connective Tissues of the Rat

Abstract: The diameters of collagen fibrils were measured in three varieties of periodontal connective tissue in the rat mandible (incisor periodontal ligament, incisor enamel-related connective tissue and molar periodontal ligament). Despite structural and functional differences between the tissues, a similar range of collagen fibril diameters was seen in each (average 45 nm). Variation between animals and between adjacent fiber bundles in any given tissue was observed. Even within any single fiber bundle, the fibrils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 17 publications
2
6
0
1
Order By: Relevance
“…Collagen fibril diameter varies between species, tissues, tissue sites and age . Previous studies have shown that the PDL fibril diameters in both rodent and human teeth are relatively small, ranging from ~45 to 55 nm . Our TEM data support that collagen fibrils have comparable diameters in mouse and human PDL (~57 nm).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Collagen fibril diameter varies between species, tissues, tissue sites and age . Previous studies have shown that the PDL fibril diameters in both rodent and human teeth are relatively small, ranging from ~45 to 55 nm . Our TEM data support that collagen fibrils have comparable diameters in mouse and human PDL (~57 nm).…”
Section: Discussionsupporting
confidence: 86%
“…35 Previous studies have shown that the PDL fibril diameters in both rodent and human teeth are relatively small, ranging from ~45 to 55 nm. 36,37 Our TEM data support that collagen fibrils have comparable diameters in mouse and human PDL (~57 nm). Tissues that are under high tension or compressive stress, such as PDL, typically have smaller diameter collagen fibrils with more interfibrillar cross-links, which facilitate the return to the tissue's original form.…”
Section: Post-translational Modifications Of Linear Crosslinking Lysupporting
confidence: 73%
“…The apparent absence of stain for collagen type VI in the mid-zone cannot be explained by a simple lack of collagenous matrix in the region, as transmission electron microscope studies (Berkovitz et al, 1981;Berkovitz & Moxham, 1989) have demonstrated a homogeneous distribution of banded collagen fbrils across the ligament. The staining pattern may, however, be related to the architecture of the banded fibrils.…”
Section: Discussionmentioning
confidence: 99%
“…This being accepted, the present data can be seen in context with analogous data derived from other tissues and species. It is well known that, in general, the collagen fibril diameter varies considerably between about 15 and 300 nm (13)(14)(15). Depending on the type of tissue, age and species, the collagen fibril diameter may also be related to the type and amount of glycosaminoglycans in the surrounding matrix as well as to the functional status of the tissue involved (15).…”
Section: Discussionmentioning
confidence: 99%
“…Respective data for collagen fibrils of the periodontal ligament are still scarce. Around continuously growing incisors and the molars of immature rats, the average collagen fibril diameter ranges between 43 and 48 nm, although 85% of the fibrils vary widely from 30 to 55 nm (14,18). Apart from the unsupported data of Gathercole & Keller (1), suggesting that collagen fibrils of the human periodontal ligament fall from about 70 nm in young to about 30 nm in old subjects, the present study provides the first comprehensive set of data on the human periodontal ligament.…”
Section: Discussionmentioning
confidence: 99%